HAP score as prognostic factor of hepatocellular carcinoma treated with transarterial chemoembolization in a Latin American center - Liza Baca, Estefanía (2018)
Introduction: Hepatocellular carcinoma (HCC) in cirrhosis is diagnosed, most of times, when it is not susceptible to curative treatment. Transarterial chemoembolization (TACE) is a palliative therapeutic option with heterogeneous results. The HAP score stratifies patients who will benefit from the first TACE. Objective: To evaluate if the HAP score is a prognostic factor of HCC treated with TACE. Materials and methods: Retrospective cohort study in cirrhotic patients with HCC and first TACE at the Edgardo Rebagliati Martins National Hospital, Lima-Peru, from June 2011 to June 20139. The HAP score was applied, mortality and survival were observed with a follow-up of 36 months. Results: We included 54 patients with age of 67.7±9.9 years, 59.3% Child-Pugh A and 40.7% Child-Pugh B, MELD score of 11±2.7; 51.9 and 40.7% were BCLC A and B, respectively; 66.7% had a single tumor and 70.4% had a predominant tumor <5cm. The HAP score classified 8, 14, 26 and 6 patients as HAP A, B, C and D, respectively. The overall survival was 19.5±11.2 months and 32.8±6.5 months for HAP A, 24.9±14.8 months for HAP B, 13.9±5.2 months for HAP C and 4±6.6 months for HAP D. There were no deaths at 12 months in HAP A. At 24 months, mortality for HAP C and D was 100%. At 36 months, the survival rate for HAP A and B was 75 and 42.9%, respectively. Conclusions: The HAP score is a useful tool to guide the management decisions of cirrhotic patients with HCC requiring TACE due to its value in predicting mortality and survival.